β-Sitosterol modulates macrophage polarization and attenuates rheumatoid inflammation in mice - Rui Liu (Taylor & Francis Group, 2019)
Context: β-Sitosterol (BS), the primary constituent of plants and vegetables, exhibits multiple biological effects. Objective: This study explores its effect of immune-regulation on macrophages and its potential for rheumatoid arthritis (RA) therapy. Materials and methods: In vitro, bone marrow-derived macrophages (BMDMs) were treated with 5, 25 and 50 μM BS in the M1 or M2 polarization conditions. In vivo, either i.p. injection with 20 or 50 mg/kg BS every 2 d after boost immunization of collagen-induced arthritis (CIA) or adoptive transfer of 2 × 106 BS-treated BMDMs (BS-BMDMs) at the day before CIA were adopted in mice to test the therapeutic effect. IL-10 antibody depletion was used in the period of above treatments to discuss the underlying mechanism. Results: The phenotypes and function of BMDMs showed that 5, 25 and 50 μM BS significantly repressed the M1 polarization and augmented M2 polarization dependent upon concentration. The expression of iNOS, IL-1β, CD86 and MHCII in 25 μM BS-treated M1-polarized BMDMs was reduced by 50.2, 47.1, 87.1 and 31.3%, respectively. In contrast, the expression of arginase-1, IL-10, CD163 and CD206 in 25 μM BS-treated M2-polarized BMDMs was increased by 65.6, 107.4, 23.5 and 51.3%, respectively. In CIA mice, either i.p. injection with BS or adoptive transfer of BS-BMDMs could alleviate the symptoms of ankle swelling (vehicle group: 3.13 ± 0.102 mm; 20 mg/kg BS group: 2.64 ± 0.043 mm; 50 mg/kg BS group: 2.36 ± 0.084 mm; BMDMs group: 3.09 ± 0.174 mm; BS-BMDMs group: 2.43 ± 0.042 mm), reduce the levels of collagen-specific antibodies (IgG and IgG1, but not IgG2c, p < 0.05) and inhibit the production of pro-inflammatory cytokines (p < 0.05). Depletion of IL-10 counteracted the effect of BS treatment (α-IL-10 vs. RatIgG1, p < 0.01 on day 16), highlighting the role of IL-10 in the anti-inflammatory response. Conclusions: These results suggested that BS could modulate the functions of macrophages and might be a promising agent for RA therapy.